Integrating Genomic and Chromosomal Data: A Cytogenetic Study of Transancistrus santarosensis (Loricariidae: Hypostominae) with Characterization of a ZZ/ZW Sex Chromosome System - Nirchio Tursellino, Mauro; de Bello Cioffi, Marcelo; de Menezes Cavalcante Sassi, Francisco; Deon, Geize Aparecida; Oliveira, Claudio [UNESP]; Kuranaka, Mariana [UNESP]; Valdiviezo-Rivera, Jonathan; Gonzalez, Víctor Hugo; Rossi, Anna Rita (MDPI, 2023)
The plecos (Loricariidae) fish represent a great model for cytogenetic investigations due to their variety of karyotypes, including diploid and polyploid genomes, and different types of sex chromosomes. In this study we investigate Transancistrus santarosensis a rare loricariid endemic to Ecuador, integrating cytogenetic methods with specimens’ molecular identification by mtDNA, to describe the the species karyotype. We aim to verify whether sex chromosomes are cytologically identifiable and if they are associated with the accumulation of repetitive sequences present in other species of the family. The analysis of the karyotype (2n = 54 chromosomes) excludes recent centric fusion and pericentromeric inversion and suggests the presence of a ZZ/ZW sex chromosome system at an early stage of differentiation: the W chromosome is degenerated but is not characterized by the presence of differential sex-specific repetitive DNAs. Data indicate that although T. santarosensis has retained the ancestral diploid number of Loricariidae, it accumulated heterochromatin and shows non-syntenic ribosomal genes localization, chromosomal traits considered apomorphic in the family.
Keywords: CGH; COI; evolution; rDNA; Siluriformes; telomeric repeats